Adherence to 24-Hour Movement Guidelines before and during COVID-19 in children: A review - Yan, Yiping; Jia, Jingjing; Liu, Bei; Ke, Youzhi; Liu, Yang (International Journal of Sports Medicine, 2025)
This study aims to describe and compare adherence to the 24-Hour Movement Guidelines (recommendations for physical activity, screen time, and sleep duration) among children before and during COVID-19 pandemic . The literature search was conducted on Web of Science, PubMed, MEDLINE, and SPORTDiscus for quantitative studies on 24-hour movement behaviors, published in English. The studies were categorized by collection date into before the pandemic (June 16th, 2016 – March 10, 2020) and during the pandemic (March 11th, 2020 – May 5, 2023), with all studies included. A random-effects model was employed to synthesize the adherence rates, and subgroup analyses were conducted based on age, sex, region, and Human development index (HDI) groups. Before the pandemic, 12.1% (95% CI:10.3%–13.9%) of overall children met the three recommendations. During the pandemic, 8.6% (95% CI: 6.4%–11.4%) of overall children met the three recommendations. The adherence to the three recommendations during the pandemic was 3.5% lower (p<0.05) than before the pandemic, with significant regional differences (p<0.05). Most children fail to meet the guidelines in any period. The adherence to the three 24-Hour Movement Guidelines during the pandemic was lower than before, with varying degrees of low adherence across different groups.
Keywords: movement behaviors; lifestyle; children; physical activity; sedentary behavior